Da responsabilidade civil extracontratual da administração pública brasileira devido a omissões : entre o monarca irresponsável e o estado segurador universal – critérios objetivos de fixação da responsabilidade estatal - Sodré, Jorge Irajá Louro (2017)
The non-contractual civil liability of the Brazilian Public Administration is informed by legal provision that attributes objective nature to it, where the legal people under domestic public law are civilly liable for the damages cause by their employees, as such, to third parties. However, since that time, doctrine and majority jurisprudence do not admit an objective public liability when the damage occurs due to a negative behavior of the Public Administration. Based on the article 15 of the Civil Code of 1916, they affirm that public liability for omission should be read subjectively, through the French theory of faute de service, whose responsibility is given when the service has not worked, or has functioned in a deficient way, or inopportunely, even admitting the anonymous fault of the Public Administration. Nevertheless, considering the constitutional maintenance of objective public liability and the validity of the Civil Code of 2002, whose rule of attribution of the liability of the State says it is objective, through a hypothetical-deductive analysis of national and foreign doctrine and jurisprudence, it was perceived that resistance to the objectification of public liability also occurs, in cases of administrative omissions, due to ideological and non-theoretical reasons, because (i) the faute de service, even in France, has its reading objectified, (ii) the investigated national jurisprudence, when judging damaging positive state behavior, motivates its judgments into the malfunctioning of the public service, not revealing that it is applying the theory of faute de service, (iii) this same jurisprudence, when analyzing administrative omissions, does it through objective criteria, and (iv) the Constitution does not make any distinction of factors of attribution of public liability. For this reason, it is concluded that rather than transplanting an alien institute, it is possible to assert a public liability for omissions in an objective way, giving the essential prevalence to the causal nexus, through the appropriate causality theory, allowing a retrospective judgment of probability, under the lights of the informative principles of Public Administration, especially those of reasonableness and efficiency, in the implementation of good public administration, the inherent obligation of the public authorities to promote the fundamental rights of people, fostering their dignity in a way that administrative actions harmonize criteria of objectivity, impartiality, justice and equity, which are provided within reasonable time, making possible the free and solidary development of each person in their society. Reasonableness requires the existence of a certain equivalence relation between the adopted measure and criteria that dimensions it, connecting the searched purpose to the means to be used with the examination of this adequacy in abstract, general and antecedent way. The efficiency in offering the concrete utilities to the citizen, in the combination of equity and efficiency of the public service, through a concerted, encouraging and negotiated action in the realization of fundamental rights.